Modified waterproof coating for roads and bridges and preparation method of modified waterproof coating
By adopting a specific formula of modified waterproof coating, the synergy between glass fiber and nanomaterials is used to solve the problem of degradation in the wear resistance of existing coatings, and the long-term wear resistance stability and overall durability of road bridges are achieved.
Patent Information
- Application Number
- CN202411990578.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-28
AI Technical Summary
When existing modified waterproof coatings face heavy traffic flows and complex use environments, their wear resistance may decline over time, affecting the connection firmness and overall durability of road bridges.
Modified waterproof coatings consisting of SBS modified asphalt, water-based polyurethane resin, nanosilica, nanoalumina, glass fiber, heavy calcium carbonate, etc. are used to form a solid mesh structure through glass fibers, nanomaterials fill pores, and water-based polyurethane resin forms a tough protective film to improve the wear resistance and stability of the coating.
It significantly improves the wear resistance of the paint, extends the maintenance cycle of road and bridges, ensures that the paint maintains good wear resistance throughout its life cycle, and improves overall durability and safety.
Smart Images

Figure CN119709014A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of waterproof coatings, in particular to a modified waterproof coating for roads and bridges and a preparation method thereof. Background Art
[0002] With the vigorous development of infrastructure construction in my country, the number and scale of road and bridge projects are constantly expanding. As a key hub of transportation, the quality and durability of roads and bridges are directly related to traffic safety and economic development. In the use of roads and bridges, waterproof protection is a vital task. Good waterproof performance can effectively prevent water from penetrating into the interior of the road and bridge structure, avoid structural corrosion, steel corrosion, concrete deterioration and other problems caused by water damage, thereby extending the service life of roads and bridges and ensuring their safe operation; current road and bridge projects are facing many severe challenges in waterproofing. On the one hand, the acceleration of urbanization has made roads and bridges bear increasingly heavy traffic loads and complex environmental factors, such as rain erosion, climate change, and alternating dry and wet conditions. Traditional waterproof protection materials and technologies are difficult to meet the long-term waterproofing needs under these harsh conditions. On the other hand, with the continuous improvement of people's requirements for the quality and durability of road and bridge projects, the existing waterproof protection measures have gradually exposed some shortcomings in practical applications, which need further improvement and innovation.
[0003] Although existing modified waterproof coatings have added wear-resistant waterproof additives and inorganic fillers to improve wear resistance, their wear resistance may still not meet the requirements of some special road and bridge parts in the face of increasingly heavy traffic flow and complex use environment; for example, in some sections with heavy traffic and a large number of heavy-loaded vehicles, or in some bridge structure parts with special mechanical friction, the wear resistance of the coating may gradually decrease over time, affecting the connection firmness and overall durability of the road bridge.
[0004] To this end, those skilled in the art have proposed a modified waterproof coating for roads and bridges and a preparation method thereof to solve the problems raised by the background technology. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a modified waterproof coating for roads and bridges and a preparation method thereof, so as to solve the problems in the prior art that the wear resistance of the modified waterproof coating will gradually decrease with the passage of time, affecting the connection firmness and overall durability of the roads and bridges.
[0006] A modified waterproof coating for roads and bridges is composed of the following raw materials in parts by weight: 30-40 parts of SBS modified asphalt, 15-25 parts of waterborne polyurethane resin, 5-10 parts of nano silicon dioxide, 3-5 parts of nano aluminum oxide, 3-8 parts of glass fiber, 10-15 parts of heavy calcium carbonate, 1-2 parts of high-efficiency dispersant, 0.5-1 parts of organosilicon defoamer, 1-2 parts of hydroxypropyl methylcellulose thickener, 1-2 parts of composite rust inhibitor, 15-25 parts of deionized water, 0.5-1 parts of stabilizer and 0.2-0.5 parts of antioxidant.
[0007] Preferably, the components of the SBS modified asphalt are as follows: 70%-85% of base asphalt, 3%-6% of SBS modifier, 0.1%-0.5% of stabilizer, and 2%-5% of compatibilizer; wherein the SBS modifier is styrene-butadiene-styrene block copolymer.
[0008] Preferably, the nano-silicon dioxide is nano-scale silicon dioxide with a particle size of 10-50 nm, and the nano-aluminum oxide is nano-scale aluminum oxide with a particle size of 5-30 nm.
[0009] Preferably, the length of the glass fiber is 3-6 mm.
[0010] Preferably, the particle size of the heavy calcium carbonate is 1-10 μm.
[0011] Preferably, the high-efficiency dispersant is sodium polyacrylate or sodium polycarboxylate.
[0012] Preferably, the organosilicon defoamer is polydimethylsiloxane or polyether-modified siloxane.
[0013] Preferably, the viscosity of the hydroxypropyl methylcellulose thickener is 10000-20000 mPa·s.
[0014] Preferably, the composite rust inhibitor is a mixture of sodium nitrite, sodium benzoate and triethanolamine, wherein sodium nitrite accounts for 30%-40%, sodium benzoate accounts for 30%-40%, and triethanolamine accounts for 20%-40%.
[0015] The preparation method of the modified waterproof coating for roads and bridges comprises the following specific steps:
[0016] S1: Prepare raw materials, weigh each raw material according to the weight ratio, ensure that the quality and purity of the raw materials meet the requirements, and set aside;
[0017] S2: Prepare SBS modified asphalt, heat 70%-85% of the base asphalt to 160-180°C to make it in a fluid state; slowly add 3%-6% of the SBS modifier, 0.1%-0.5% of the stabilizer and 2%-5% of the phase solvent under stirring; continue stirring and keep the temperature at 170-180°C, perform shearing, stirring and other processes to fully mix the components, the reaction time is 30-60 minutes, and the SBS modified asphalt is prepared;
[0018] S3: Mix the main components, add the prepared SBS modified asphalt, waterborne polyurethane resin, nano silicon dioxide, nano aluminum oxide, glass fiber, heavy calcium carbonate, high-efficiency dispersant, composite rust inhibitor, stabilizer and antioxidant into a high-speed disperser, and stir at a speed of 500-800 rpm for 15-30 minutes to preliminarily mix the components;
[0019] S4: Defoaming treatment: during the stirring process, slowly add the silicone defoamer and continue stirring for 10-15 minutes to eliminate bubbles in the mixture and ensure the surface smoothness of the coating;
[0020] S5: thickening and adjusting, adding hydroxypropyl methylcellulose thickener, stirring at a speed of 200-300 rpm for 5-10 minutes, and adjusting the viscosity of the mixture to achieve a construction performance of 10000-20000 mPa·s;
[0021] S6: dilute and disperse, gradually add deionized water, continue stirring, the stirring speed is 300-500 rpm, the stirring time is 20-30 minutes, and ensure that all components are fully dispersed and mixed evenly;
[0022] S7: Filtration and packaging: the prepared coating is passed through filtering equipment to remove possible impurities and particles, ensure the quality of the coating, and store it for future use.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] This material forms a solid mesh structure through glass fiber, which effectively resists friction and wear caused by vehicles, pedestrians and natural factors; nano-silicon dioxide and nano-alumina fill pores, enhance surface hardness and wear resistance, and work together with glass fiber to improve the wear resistance of the coating from micro to macro, and the nano-material has good stability to prevent the wear resistance from decreasing over time; water-based polyurethane resin forms a tough protective film on the surface of the coating to buffer external impact and wear, and has a significant effect on sections that are frequently subject to vehicle braking and starting friction; nano-alumina and water-based polyurethane resin produce hydrogen bonding and chemical bonding, etc., increase the interface bonding force, improve the overall stability and adhesion of the coating, and make the coating firmly adhere to the surface of the road and bridge, reducing the possibility of shedding. The raw material ratio is precisely controlled to ensure that the coating maintains good wear resistance throughout its life cycle, and the decline rate is significantly slowed compared with traditional coatings. In addition to preventing the metal substrate from rusting, the composite rust inhibitor also indirectly enhances the stability of the wear resistance of the coating and ensures that the coating is firmly bonded to the metal. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is a schematic diagram of the overall structure of the present invention. DETAILED DESCRIPTION
[0026] The following embodiments of the present invention are described in further detail in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.
[0027] Embodiment 1: As shown in the attached Figure 1 As shown: The present invention provides a modified waterproof coating for roads and bridges, which is composed of the following raw materials in parts by weight: 30-40 parts of SBS modified asphalt, 15-25 parts of water-based polyurethane resin, 5-10 parts of nano silicon dioxide, 3-5 parts of nano aluminum oxide, 3-8 parts of glass fiber, 10-15 parts of heavy calcium carbonate, 1-2 parts of high-efficiency dispersant, 0.5-1 parts of organosilicon defoaming agent, 1-2 parts of hydroxypropyl methylcellulose thickener, 1-2 parts of composite rust inhibitor, 15-25 parts of deionized water, 0.5-1 parts of stabilizer and 0.2-0.5 parts of antioxidant.
[0028] The components of SBS modified asphalt are as follows: base asphalt 70%-85%, SBS modifier 3%-6%, stabilizer 0.1%-0.5%, compatibilizer 2%-5%; wherein the SBS modifier is styrene-butadiene-styrene block copolymer.
[0029] Nano silicon dioxide uses nano silicon dioxide with a particle size of 10-50nm, and nano aluminum oxide uses nano aluminum oxide with a particle size of 5-30nm.
[0030] The length of the glass fiber is 3-6 mm; the particle size of the heavy calcium carbonate is 1-10 μm; the high-efficiency dispersant is sodium polyacrylate or sodium polycarboxylate; and the organosilicon defoaming agent is polydimethylsiloxane or polyether-modified siloxane.
[0031] The viscosity of the hydroxypropyl methylcellulose thickener is 10000-20000 mPa·s; the composite rust inhibitor is a mixture of sodium nitrite, sodium benzoate and triethanolamine, wherein sodium nitrite accounts for 30%-40%, sodium benzoate accounts for 30%-40%, and triethanolamine accounts for 20%-40%.
[0032] The glass fiber is evenly dispersed in the paint to form a solid mesh structure, which can effectively withstand friction and wear caused by various factors such as vehicle driving, pedestrian trampling and natural environment; its high strength and wear resistance provide basic wear-resistant support for the paint. During long-term use, the glass fiber can continue to play a role, resist external wear forces, reduce coating loss, and thus maintain the stability of the paint's wear resistance; in actual application scenarios, after a long period of traffic flow, the surface wear of the paint coating containing glass fiber is significantly lower than that of ordinary paint, maintaining the integrity and smoothness of the road and bridge surface.
[0033] Nanomaterials such as nano-silica and nano-alumina, due to their small particle size and large specific surface area, can fill the tiny pores in the coating to form a denser structure, thereby improving the waterproof barrier properties of the coating and enhancing its surface hardness and wear resistance. Nanomaterials and glass fibers work together to comprehensively improve the wear resistance of the coating from the microscopic to the macroscopic level, and during long-term use, the stability of the nanomaterials enables it to continuously maintain this enhancement effect, effectively preventing the problem of wear resistance decreasing over time.
[0034] Waterborne polyurethane resin has good flexibility and wear resistance, and forms a tough protective film on the surface of the coating; this protective film can not only improve the initial wear resistance of the coating, but also buffer the impact and wear of the coating by external forces through its own elasticity and wear resistance during long-term use, further protect the internal structure of the coating, and maintain the stability of the wear resistance. For example, in some road bridge sections that are frequently subjected to vehicle braking and starting friction, the wear of the coating surface has been significantly improved after using this coating, proving the important role of waterborne polyurethane resin in maintaining long-term wear resistance.
[0035] The waterborne polyurethane resin molecules contain a large number of polar groups, such as carbamate groups (-NHCOO-) and urea groups (-NHCONH-). The hydrogen atoms in the groups form hydrogen bonds with the oxygen atoms on the surface of nano-alumina. There are functional groups such as hydroxyl groups (-OH) on the surface of nano-alumina. The hydroxyl groups can act as hydrogen bond acceptors or donors to interact with the corresponding groups in the waterborne polyurethane resin. The formation of hydrogen bonds increases the interfacial bonding force between nano-alumina and waterborne polyurethane resin, so that during the film formation process of the coating, the nano-alumina can be better dispersed and embedded in the resin matrix, thereby improving the overall stability of the coating. The enhanced interfacial bonding force helps to improve the adhesion of the coating, so that the coating can be more firmly attached to the surface of roads and bridges, reducing the possibility of the coating falling off due to external forces during use. A stronger connection is formed between the nano-alumina and the waterborne polyurethane resin, which significantly improves the mechanical properties of the coating, including tensile strength.
[0036] By precisely controlling the proportions of the various raw materials, the synergistic effects between them are optimized, ensuring that the coating maintains good wear resistance throughout its entire service life. In simulation tests conducted under different usage environments and traffic conditions, the coating prepared according to the formula of the present invention always exhibits stable wear resistance, and compared with traditional coatings, the rate of decline in its wear resistance is significantly slowed, effectively extending the maintenance cycle of roads and bridges.
[0037] The composite rust inhibitor can prevent the metal substrate from rusting, improve the overall structural safety of roads and bridges, and also have a certain indirect effect on the maintenance of wear resistance. It can form a protective film in the coating to prevent oxygen and moisture from contacting the metal substrate. At the same time, it also reduces the erosion of these factors on the interface between the coating and the metal substrate, thereby ensuring the adhesion of the coating to the metal surface and indirectly enhancing the wear resistance and stability of the coating. Because if the interface between the coating and the metal substrate is damaged, the wear resistance of the coating will also be affected. In actual applications, after long-term use, the bonding between the metal parts of the road bridge using this coating and the coating coating is still strong, and the wear resistance is effectively guaranteed.
[0038] SBS modified asphalt has good adhesion and can be closely combined with the base material on the surface of roads and bridges to form a strong bonding interface; after the coating is applied, SBS modified asphalt can penetrate into the tiny pores of the base layer and form a variety of bonding methods such as mechanical anchoring and chemical bonding with the base layer, thereby greatly improving the adhesion between the coating and the base layer; this strong adhesion makes it difficult for the coating to peel off from the base layer when subjected to various external forces, ensuring the integrity and stability of the road and bridge coating, thereby enhancing the connection firmness of the road and bridge. Improve overall durability
[0039] In addition to excellent wear resistance, this coating also has good waterproof, weather resistance and rust resistance. The waterproof performance prevents moisture from penetrating into the interior of the structure, reducing structural corrosion and deterioration caused by water damage. The weather resistance enables the coating to adapt to different climatic conditions and resist erosion by natural factors such as sunlight, rain, and temperature changes. The rust resistance protects metal parts from rusting and maintains the integrity and stability of the structure. The synergistic effect of these comprehensive properties enables roads and bridges to remain in good condition during long-term use, improving overall durability and safety.
[0040] From the above, we can know that the following raw materials should be accurately weighed:
[0041] 30 parts of SBS modified asphalt (including 22.5 parts of base asphalt, 1.5 parts of SBS modifier, 0.09 parts of stabilizer and 1.41 parts of compatibilizer); 15 parts of waterborne polyurethane resin; 5 parts of nano-silicon dioxide (particle size 10-50nm); 3 parts of nano-alumina (particle size 5-30nm); 3 parts of glass fiber (length 3-6mm); 10 parts of heavy calcium carbonate (particle size 1-10μm); 1 part of high-efficiency dispersant (sodium polyacrylate); 0.5 parts of organosilicon defoaming agent (polydimethylsiloxane); 1 part of hydroxypropyl methylcellulose thickener (viscosity 10000-20000mPa·s); composite rust inhibitor (0.3 parts of sodium nitrite, 0.4 parts of sodium benzoate and 0.3 parts of triethanolamine); 15 parts of deionized water; 0.5 parts of stabilizer (polyvinyl alcohol); 0.2 parts of antioxidant (butylated hydroxytoluene).
[0042] The preparation process is as follows:
[0043] Heat 22.5 parts of base asphalt to 160-180°C, and slowly add 1.5 parts of SBS modifier, 0.09 parts of stabilizer and 1.41 parts of phase solvent while stirring.
[0044] The temperature is maintained at 170-180°C, stirring is continued and shearing and other processes are performed, and the reaction time is 30-60 minutes to obtain SBS modified asphalt.
[0045] Add the prepared SBS modified asphalt and other raw materials (waterborne polyurethane resin, nano silicon dioxide, nano aluminum oxide, glass fiber, heavy calcium carbonate, high-efficiency dispersant, composite rust inhibitor, stabilizer and antioxidant) into a high-speed disperser.
[0046] Stir at a speed of 500-800 rpm for 15-30 minutes to make the components preliminarily mixed evenly; slowly add 0.5 parts of silicone defoamer (polydimethylsiloxane) during the stirring process, and continue stirring for 10-15 minutes to eliminate bubbles;
[0047] Add 1 part of hydroxypropyl methylcellulose thickener, stir at 200-300 rpm for 5-10 minutes, and adjust the viscosity to 10000-20000 mPa·s;
[0048] Gradually add 15 parts of deionized water and continue stirring at 300-500 rpm for 20-30 minutes to ensure that all components are fully dispersed and mixed;
[0049] The prepared coating is passed through a filtering device to remove impurities and particles and then stored for future use.
[0050] The performance parameters of the prepared coating are as follows:
[0051] Appearance: Uniform and delicate paste without obvious particles and impurities.
[0052] Density: 1.2-1.3g / cm 3 .
[0053] Solid content: ≥70%.
[0054] Tensile strength: ≥2.0MPa.
[0055] Elongation at break: ≥300%.
[0056] Wear resistance: tested by Taber wear tester, wear amount ≤0.1g / 1000 revolutions.
[0057] Waterproofness: 0.3MPa, no leakage for 30min.
[0058] Waterproof grade: P8.
[0059] Weather resistance: Artificial accelerated aging test (xenon lamp aging): After 500h, the tensile strength retention rate is ≥80%, and the elongation at break retention rate is ≥70%.
[0060] The specific preparation steps of SBS modified asphalt are as follows:
[0061] Prepare raw materials: base asphalt, SBS modifier, stabilizer, and compatibilizer.
[0062] Heating base asphalt: Heat the base asphalt to a certain temperature to make it have better fluidity, generally heated to 160-180℃.
[0063] Adding SBS modifier and stabilizer: slowly add SBS modifier and stabilizer into the heated base asphalt while stirring to mix them thoroughly.
[0064] Shear grinding: Use high-speed shearing machine or colloid mill to shear and grind the mixed asphalt, so that the SBS modifier is evenly dispersed in the asphalt to form a stable system; the time and speed of shear grinding are adjusted according to the equipment and process requirements, and it takes 15-30 minutes.
[0065] Development: The sheared and ground asphalt is developed at a certain temperature to allow the SBS modifier to fully react with the asphalt and improve the modification effect; the development time is 1-2 hours and the temperature is maintained at 170-190°C.
[0066] Adjusting properties: According to needs, appropriate amount of compatibilizer or other additives can be added to adjust the properties of SBS modified asphalt, such as softening point, needle penetration, elongation, etc.
[0067] Testing and storage: The prepared SBS modified asphalt is quality tested to ensure that it meets the relevant standards and requirements. After passing the test, the SBS modified asphalt is stored at an appropriate temperature, away from direct sunlight and high temperature environment, to ensure its stable performance.
[0068] Embodiment 2:
[0069] Weigh the following raw materials: 35 parts of SBS modified asphalt (including 28 parts of base asphalt, 1.4 parts of SBS modifier, 0.14 parts of stabilizer, and 1.96 parts of compatibilizer); 20 parts of waterborne polyurethane resin; 8 parts of nano-silicon dioxide (particle size 10-50nm); 4 parts of nano-alumina (particle size 5-30nm); 5 parts of glass fiber (length 3-6mm); 12 parts of heavy calcium carbonate (particle size 1-10μm); high-efficiency dispersed 1.5 parts of agent (sodium polycarboxylate); 0.8 parts of silicone defoaming agent (polyether modified siloxane); 1.5 parts of hydroxypropyl methylcellulose thickener (viscosity 10000-20000mPa·s); composite rust inhibitor (0.35 parts of sodium nitrite, 0.35 parts of sodium benzoate, 0.3 parts of triethanolamine); 20 parts of deionized water; 0.8 parts of stabilizer (sodium carboxymethyl cellulose); 0.3 parts of antioxidant (butylated hydroxyanisole).
[0070] The preparation process is as follows:
[0071] Heat 28 parts of base asphalt to 160-180°C, and slowly add 1.4 parts of SBS modifier, 0.14 parts of stabilizer and 1.96 parts of compatibilizer under stirring;
[0072] Stirring at 170-180°C and performing relevant process treatment, reacting for 30-60 minutes, to obtain SBS modified asphalt;
[0073] Put SBS modified asphalt and other raw materials (waterborne polyurethane resin, nano silicon dioxide, nano alumina, glass fiber, heavy calcium carbonate, high-efficiency dispersant, composite rust inhibitor, stabilizer and antioxidant) into a high-speed disperser;
[0074] Stir at a speed of 500-800 rpm for 15-30 minutes. Preliminary mixing is performed and 0.8 parts of organosilicon defoamer (polyether modified siloxane) is slowly added during stirring. Stir for 10-15 minutes to defoam.
[0075] Add 1.5 parts of hydroxypropyl methylcellulose thickener and stir at 200-300 rpm for 5-10 minutes to adjust the viscosity;
[0076] Gradually add 20 parts of deionized water, stir at a speed of 300-500 rpm for 20-30 minutes to fully disperse and mix, filter through a filtering device and store for later use.
[0077] The performance parameters of the prepared coating are as follows:
[0078] Appearance: Uniform and delicate paste without obvious particles and impurities.
[0079] Density: 1.25-1.35g / cm 3 .
[0080] Solid content: ≥75%.
[0081] Tensile strength: ≥2.5MPa.
[0082] Elongation at break: ≥350%.
[0083] Wear resistance: tested by Taber wear tester, wear amount ≤0.08g / 1000 revolutions.
[0084] Waterproofness: 0.4MPa, no leakage for 30min.
[0085] Waterproof grade: P10.
[0086] Artificial accelerated aging test (xenon lamp aging): After 500h, the tensile strength retention rate is ≥85%, and the elongation at break retention rate is ≥75%.
[0087] Embodiment 3
[0088] Accurately weigh the following ingredients:
[0089] SBS modified asphalt 40 parts (including base asphalt 34 parts, SBS modifier 1.2 parts, stabilizer 0.2 parts, compatibilizer 1.8 parts), waterborne polyurethane resin 25 parts, nano silicon dioxide (particle size 10-50nm) 10 parts, nano aluminum oxide (particle size 5-30nm) 5 parts, glass fiber (length 3-6mm) 8 parts, heavy calcium carbonate (particle size 1-10μm) 15 parts, high-efficiency dispersant (sodium polyacrylate and sodium polycarboxylate 1 part each) 2 parts, silicone 1 part of defoaming agent (0.5 parts each of polydimethylsiloxane and polyether modified siloxane), 2 parts of hydroxypropyl methylcellulose thickener (viscosity 10000-20000mPa·s), 0.4 parts of composite rust inhibitor (0.3 parts of sodium nitrite, 0.3 parts of sodium benzoate, 0.3 parts of triethanolamine), 25 parts of deionized water, 1 part of stabilizer (0.5 parts each of polyvinyl alcohol and sodium carboxymethyl cellulose), and 0.5 parts of antioxidant (0.25 parts each of butylated hydroxytoluene and butylated hydroxyanisole).
[0090] The preparation process is as follows:
[0091] Heat 34 parts of base asphalt to 160-180°C, and slowly add 1.2 parts of SBS modifier, 0.2 parts of stabilizer and 1.8 parts of compatibilizer while stirring;
[0092] Stirring and performing process operation at 170-180°C for 30-60 minutes to prepare SBS modified asphalt;
[0093] Add the prepared SBS modified asphalt and other raw materials (waterborne polyurethane resin, nano silicon dioxide, nano aluminum oxide, glass fiber, heavy calcium carbonate, high-efficiency dispersant, composite rust inhibitor, stabilizer and antioxidant) into a high-speed disperser;
[0094] Stir at a speed of 500-800 rpm for 15-30 minutes to allow the components to be initially evenly mixed;
[0095] During the stirring process, slowly add 1 part of silicone defoamer (0.5 parts each of polydimethylsiloxane and polyether modified silicone), and continue stirring for 10-15 minutes to eliminate bubbles; add 2 parts of hydroxypropyl methylcellulose thickener, stir at 200-300 rpm for 5-10 minutes, and adjust to the appropriate viscosity.
[0096] Gradually add 25 parts of deionized water, continue stirring at 300-500 rpm for 20-30 minutes to ensure sufficient dispersion and mixing, filter with a filtering device and store for later use.
[0097] The performance parameters of the prepared coating are as follows:
[0098] Appearance: Uniform and delicate paste without obvious particles and impurities.
[0099] Density: 1.3-1.4g / cm 3 .
[0100] Solid content: ≥80%.
[0101] Tensile strength: ≥3.0MPa.
[0102] Elongation at break: ≥400%.
[0103] Wear resistance: tested by Taber wear tester, wear amount ≤0.06g / 1000 revolutions.
[0104] Waterproofness: 0.5MPa, no leakage for 30min.
[0105] Waterproof grade: P12.
[0106] Artificial accelerated aging test (xenon lamp aging): After 500h, the tensile strength retention rate is ≥90%, and the elongation at break retention rate is ≥80%.
[0107] The embodiments of the present invention are provided for the purpose of illustration and description. Although the embodiments of the present invention have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations of the present invention. Ordinary technicians in this field can change, modify, replace and deform the above embodiments within the scope of the present invention.
[0108] In the description of the present invention, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. "Multiple" means two or more, unless otherwise clearly and specifically defined.
[0109] In the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0110] In the present invention, unless otherwise clearly specified and limited, a first feature being "above" or "below" a second feature may mean that the first and second features are in direct contact, or the first and second features are in indirect contact through an intermediate medium. Moreover, a first feature being "above", "above" or "above" a second feature may mean that the first feature is directly above or obliquely above the second feature, or simply means that the first feature is higher in level than the second feature. A first feature being "below", "below" or "below" a second feature may mean that the first feature is directly below or obliquely below the second feature, or simply means that the first feature is lower in level than the second feature.
[0111] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "examples", "specific examples" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine different embodiments or examples described in this specification and the features of different embodiments or examples, unless they are contradictory.
[0112] In the drawings of the embodiments disclosed in the present invention, only the structures involved in the embodiments disclosed in the present invention are involved, and other structures can refer to the general design. In the absence of conflict, the same embodiment and different embodiments of the present invention can be combined with each other.
[0113] Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A modified waterproof coating for roads and bridges, characterized in that: The invention is composed of the following raw materials in parts by weight: 30-40 parts of SBS modified asphalt, 15-25 parts of waterborne polyurethane resin, 5-10 parts of nano silicon dioxide, 3-5 parts of nano aluminum oxide, 3-8 parts of glass fiber, 10-15 parts of heavy calcium carbonate, 1-2 parts of high-efficiency dispersant, 0.5-1 parts of organosilicon defoamer, 1-2 parts of hydroxypropyl methylcellulose thickener, 1-2 parts of composite rust inhibitor, 15-25 parts of deionized water, 0.5-1 parts of stabilizer and 0.2-0.5 parts of antioxidant.
2. A modified waterproof coating for roads and bridges as claimed in claim 1, characterized in that: The components of the SBS modified asphalt are as follows: 70%-85% of base asphalt, 3%-6% of SBS modifier, 0.1%-0.5% of stabilizer, and 2%-5% of compatibilizer; wherein the SBS modifier is styrene-butadiene-styrene block copolymer.
3. A modified waterproof coating for roads and bridges as claimed in claim 2, characterized in that: The nano silicon dioxide is nano silicon dioxide with a particle size of 10-50nm, and the nano aluminum oxide is nano aluminum oxide with a particle size of 5-30nm.
4. A modified waterproof coating for roads and bridges as claimed in claim 2, characterized in that: The length of the glass fiber is 3-6 mm.
5. The modified waterproof coating for roads and bridges according to claim 2, characterized in that: The particle size of the heavy calcium carbonate is 1-10 μm.
6. The modified waterproof coating for roads and bridges according to claim 2, characterized in that: The high-efficiency dispersant is sodium polyacrylate or sodium polycarboxylate.
7. The modified waterproof coating for roads and bridges according to claim 2, characterized in that: The organosilicon defoamer is polydimethylsiloxane or polyether modified siloxane.
8. The modified waterproof coating for roads and bridges according to claim 2, characterized in that: The viscosity of the hydroxypropyl methylcellulose thickener is 10000-20000 mPa·s.
9. The modified waterproof coating for roads and bridges according to claim 1, characterized in that: The composite rust preventive is a mixture of sodium nitrite, sodium benzoate and triethanolamine, wherein sodium nitrite accounts for 30%-40%, sodium benzoate accounts for 30%-40%, and triethanolamine accounts for 20%-40%.
10. A method for preparing a modified waterproof coating for roads and bridges according to any one of claims 1 to 9, characterized in that: The specific steps are: S1: Prepare raw materials, weigh each raw material according to the weight ratio, ensure that the quality and purity of the raw materials meet the requirements, and set aside; S2: Prepare SBS modified asphalt, heat 70%-85% of the base asphalt to 160-180°C to make it in a fluid state; slowly add 3%-6% of the SBS modifier, 0.1%-0.5% of the stabilizer and 2%-5% of the phase solvent under stirring; continue stirring and keep the temperature at 170-180°C, perform shearing, stirring and other processes to fully mix the components, the reaction time is 30-60 minutes, and the SBS modified asphalt is prepared; S3: Mix the main components, add the prepared SBS modified asphalt, waterborne polyurethane resin, nano silicon dioxide, nano aluminum oxide, glass fiber, heavy calcium carbonate, high-efficiency dispersant, composite rust inhibitor, stabilizer and antioxidant into a high-speed disperser, and stir at a speed of 500-800 rpm for 15-30 minutes to preliminarily mix the components; S4: Defoaming treatment: during the stirring process, slowly add the silicone defoamer and continue stirring for 10-15 minutes to eliminate bubbles in the mixture and ensure the surface smoothness of the coating; S5: thickening and adjusting, adding hydroxypropyl methylcellulose thickener, stirring at a speed of 200-300 rpm for 5-10 minutes, and adjusting the viscosity of the mixture to achieve a construction performance of 10000-20000 mPa·s; S6: dilute and disperse, gradually add deionized water, continue stirring, the stirring speed is 300-500 rpm, the stirring time is 20-30 minutes, and ensure that all components are fully dispersed and mixed evenly; S7: Filtration and packaging: the prepared coating is passed through filtering equipment to remove possible impurities and particles, ensure the quality of the coating, and store it for future use.
Citation Information
Cited By
Environment-friendly anti-coating washable coating and preparation method thereof
CN122037633A